The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/rcm.927
|View full text |Cite
|
Sign up to set email alerts
|

Heuristic charge assignment for deconvolution of electrospray ionization mass spectra

Abstract: We propose a new algorithm for deconvolution of electrospray ionization mass spectra based on direct assignment of charge to the measured signal at each mass-to-charge ratio (m/z). We investigate two heuristics for charge assignment: the entropy-based heuristic is adapted from a deconvolution algorithm by Reinhold and Reinhold;10 the multiplicative-correlation heuristic is adapted from the multiplicative-correlation deconvolution algorithm of Hagen and Monnig.6 The entropy-based heuristic is insensitive to ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 10 publications
1
31
0
Order By: Relevance
“…A number of different algorithms have been developed for deconvoluting electrospray mass spectra [2632]. Although a detailed comparison is beyond the scope of this report, our probability-based deconvolution (PBD) has conceptual and algorithmic differences from the entropy-based methods such as MaxEnt [26,27] and the algorithm developed by Reinhold and Reinhold [30].…”
Section: Resultsmentioning
confidence: 99%
“…A number of different algorithms have been developed for deconvoluting electrospray mass spectra [2632]. Although a detailed comparison is beyond the scope of this report, our probability-based deconvolution (PBD) has conceptual and algorithmic differences from the entropy-based methods such as MaxEnt [26,27] and the algorithm developed by Reinhold and Reinhold [30].…”
Section: Resultsmentioning
confidence: 99%
“…It has long been assumed that HNE predominantly forms Schiffbase adducts with lysine residues: this first mass spectrometric evidence of HNE-protein interaction via Michael addition was confirmed by different analytical approaches such as quantitative conversion of the modified proteins to oxime and pentafluorobenzyl oxime derivatives and subsequent ESI-MS analysis, spectrophotometric protein carbonyl analysis, and GC-MS determination of HNE released upon treatment with hydroxylamine. The preponderance of Michael addition products over Schiff base adducts also indicates that most of the existing methods for determining HNE adducts in biological tissues or fluids, based on the use of hydrazines or hydroxylamines to dis- The ESI-MS analysis coupled to maximum entropy algorithm (Zheng et al, 2003) was found suitable to give unequivocal evidence of the stoichiometry of reaction and to determine Michael versus Schiff base adduction mechanism of HNE (156 Da vs. 138 Da increment), but it did not give information on the amino acid residues (histidine, cysteine, or lysine) involved in the Michael addition.…”
Section: A Hemoproteinsmentioning
confidence: 99%
“…For data acquired with the “Low/High” strategy, intact precursor and fragment masses from .raw files were determined using in-house software (called ‘cRAWler’) to generate files for ProSightPC 2.0. This software uses an embedded version of the deconvolution algorithm26 for determining average, neutral intact masses and the ‘THRASH’27 algorithm for extracting monoisotopic, neutral fragment masses. These data in .puf ( P roSight u pload f ormat) files were searched against a shotgun-annotated human (754,012 protein forms) or yeast (52,616 protein forms) proteome databases containing known post-translational modifications and alternative splice forms.…”
Section: Methodsmentioning
confidence: 99%